Analisis Pengelolaan Sistem E-Office Kepegawaian di Kantor Kelurahan Rawamangun Kecamatan Pulogadung Kota Administrasi Jakarta Timur - Ahmad Bayhaki; Kiki Setyawati; Sari Ningsih (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
Digital personnel administration has become an important instrument for improving efficiency, accuracy, and service quality within public organizations. However, its implementation is often influenced by technological readiness, employee competence, organizational support, and the ability of users to adapt to digital systems. This study aims to analyze the management of the e-office personnel system at the Rawamangun Urban Village Office, Pulogadung District, East Jakarta Administrative City, including the obstacles encountered and the efforts undertaken to address them. The study employed a descriptive qualitative approach. Seven informants were selected purposively based on their roles, experience, and involvement in operating the e-office personnel system. Data were collected through interviews, observation, and documentation, then analyzed through data reduction, data display, conclusion drawing, and verification. The findings show that e-office management supports personnel administration by simplifying document processing, improving data accessibility, and increasing administrative efficiency. Its implementation is influenced by information technology infrastructure, employee competence, system security, internal organizational support, and workplace culture. The main obstacles include limited technological adaptability among some employees, particularly senior staff, and unstable internet connectivity. To address these problems, the office provides employee training, technical assistance, periodic system evaluation, and knowledge transfer between technologically proficient employees and colleagues requiring support. These efforts are essential for strengthening digital competence and ensuring the sustainable implementation of the e-office personnel system.